Wajah Laut dalam Sastra Indonesia, Perspektif Blue Cultural Studies: Menikmati Ikan-ikan Hiu, Ido, dan Homa-nya YB Mangunwijaya - Anas Ahmadi (HISKI, 2017)
In this study explained Indonesian literature through blue cultural studies perspective. Therefore, in this study refers to the views Mentz (2009) on blue cultural studies. Sources of data in this study is Ikan-ikan Hiu, Ido, dan Homaby Mangunwijaya (2015). The results showed that the daily life of people Mangunwijaya featuring sailors and pirates on Halmahera. He (Mangunwijaya) symbolizes human life such as sharks, Ido, and homa, there are ‘predators’, ‘conquered’, or ‘betrayer’.